NILAI BUDAYA BAHASA RITUAL PERANG TANDING PADA ETNIK LAMAHOLOT DI PULAU ADONARA, FLORES TIMUR - Sabon Ola, Simon (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2008)
Abstract Cultural perceptions and values act as a guide to the behavior of a community. This is explained in this article in which the spotlight is focused on a description of the duel ritual among the Lamaholot people. Based on the concept that culture and language are linked, this article contains an explanation of the perceptions of the Lamaholot people towards the duel and the cultural values which are implied in the story of the ritual. The Lamaholot people view the duel as a mechanism for proving one real self. This is closely connected to the cultural value which is contained in the story of the duel ritual. The cultural values that are implied are: self-awareness, justness as a foundation for humanity, and a belief in the role of the ancestors.